Moderating role of affective factors on relationship between vocabulary learning strategies use and vocabulary performance - Abozaid, Laila Aiyad Ali (2020)
Vocabulary is a vital aspect of all language skills: reading, writing, listening, and speaking. However, many Libyan undergraduates display various problems when encountering vocabulary in English. In order to develop Libyan students' vocabulary, there is a need to improve their strategies for learning vocabulary as it influences learning English in general. Therefore, the aim of this research is to examine the moderating role of affective factors on relationship between vocabulary learning strategies use and vocabulary performance. The first objective of this study was to identify the level of learners’ vocabulary learning strategies (VLSs) use, learners’ affective factors (selfefficacy beliefs, learners’ attitudes, learners’ anxiety, and learners’ self-regulating capacity), and the productive and receptive vocabulary knowledge of the respondents. It also tested the significance of the relationship between the selected Libyan learners’ affective factors and their use of vocabulary learning strategies. Furthermore, it determined the significance of learners’ affective factors in their productive and receptive vocabulary performance. The results were obtained through investigation of the moderating role of affective factors on relationship between VLS use and vocabulary performance. A total number of 200 Libyan EFL undergraduate students participated in the study, who were selected from a Libyan public university (Tripoli University). In this study, the data was collected through two sets of questionnaires. The first one was adopted from Schmitt’s (1997) Vocabulary Learning Strategies Questionnaire (VLSQ). The second one was adapted from Tseng’s (2006) Initial Appraisal of Vocabulary Learning Experience and Self-Regulating Capacity in Vocabulary Learning (IAVLE &SRCvoc). The Productive Vocabulary Levels Test (PVLT) by Laufer and Nation (1999) and the Vocabulary Size Test (VST) by Nation and Belgar (2007) were adopted to achieve the goals of the study. Data was analysed quantitatively using the Statistical Package for the Social Sciences version 25.Frequency counts, mean scores, and standard deviations were used to analyse students’ frequency of vocabulary learning strategies, students’ level of affective factors and students’ vocabulary performance. The research also employed Pearson correlation to determine the relationships between variables. Furthermore, multiple regression analyses were performed to find the effect of affective factors on the relationship between vocabulary learning strategies use and vocabulary performance. The findings show that the respondents were determined as medium-level strategy users with a mean score of 3.4 and standard deviation of 0.5 for overall strategy use. The findings also show positive relationships between variables: the overall vocabulary learning strategies were significantly related to self-efficacy, attitude, anxiety, and selfregulation; learners’ scores of vocabulary size were significantly related to affective factors; and a statistically significant relationship between learners’ vocabulary performance and their use of vocabulary learning strategies was found. In addition, the findings reveal that there is a moderating role of self-regulation on relationship between vocabulary learning strategies use and vocabulary performance. The results indicate that vocabulary learning strategies and vocabulary performance can improve through the integration of self-regulation.